OPTIMASI RANCANGAN MESIN PENGERING TEMBAKAU DENGAN MENGGUNAKAN TUBULAR FIN HEATER - Vincentius Glenaudi Favian Silaban (2021)
Tobacco is one of the most important leaflets in Indonesia's Agricultural sector, because the consumer of tobacco products which is ciggaretes have a high number, with many traditional tobacco producers/homemade using the sun's heat for drying process, can be said to be not efficient in the rainy season. Technology innovation that are soluble to efficiency are critical concentrations to discuss in this discussion. Optimization of the design this time to get the ideal shape / design of the oven cabinet dryer that has ever existed, by changing the dimensions of the machine and the tools used to generate heat using a Tubular Fin Heater by utilizing electrical energy that is converted into heat energy and channeled using a DC fan to generate heat. throughout the drying chamber. Tobacco dryer products using Tubular Fin Heater can be used as an alternative tool that is economical and efficient and safe to use, as well as partitions that are very easy to obtain so as to increase the number of tobacco production in the market.